Aplikasi WiMAX - Yenniwarti Rafsyam; Milda Yuliza; Lifwarda Lifwarda (Elektron : Jurnal Ilmiah, 2009)
WiMAX is Broadband Wireless Acces (BWA) technology evolution with interactive fitur. WiMAX not only have issue about data speed problem but also about open standard. It means, communications between WiMax instruments between some different vendors are not proprietary. WimAX orientations are not only for fixed market, but also for portable and mobile market. WiMAX with high speed data (up to 70 MBps) is suitable to apply in last mile broadband connections, backhaul and high speed enterprise.